2007
DOI: 10.1623/hysj.52.6.1119
|View full text |Cite
|
Sign up to set email alerts
|

Hydrological impact simulations of climate change on Lebanese coastal rivers /Simulations des impacts hydrologiques du changement climatique sur les fleuves côtiers Libanais

Abstract: The significance of predicted climatic changes is still uncertain. The hydrological consequences of climatic changes on Lebanese catchments are analysed by means of different scenarios of rainfall variability and temperature increase. The conceptual rainfall-runoff model MEDOR, coupled to a stochastic model of rainfall and temperature, is used to estimate change in runoff by simulation of six scenarios. These test the response to the rainfall structure, to the duration of rainy events, their frequency, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Hreiche et al 2007, Fujihara et al 2008, Senatore et al 2011, Ruelland et al 2012. However, Cudennec et al (2007) have shown that the Mediterranean region is particularly sensitive to changes brought about by human pressure on hydrological processes.…”
Section: Introductionmentioning
confidence: 99%
“…Hreiche et al 2007, Fujihara et al 2008, Senatore et al 2011, Ruelland et al 2012. However, Cudennec et al (2007) have shown that the Mediterranean region is particularly sensitive to changes brought about by human pressure on hydrological processes.…”
Section: Introductionmentioning
confidence: 99%
“…Socioeconomically, and as other regions of Lebanon, the Nahr Ibrahim basin presents a densely populated lower portion corresponding to its coastal area in contrast to a less populated upper mountainous region [10]. In addition to urbanization in its lower part, the Nahr Ibrahim basin suffers from intensive industrial development [84] as opposed to a much less populated mountainous upper part.…”
Section: The Nahr Ibrahim Basin: a Representative Mediterranean Basinmentioning
confidence: 99%
“…Climate change is expected to have severe consequences on Mediterranean runoff with a serious risk of fresh water availability decrease of 2% to 15% for 2°C of warming (Cramer et al, 2018) and significant increase of droughts period particularly in the South and East (Hreiche et al, 2007;Cudennec et al, 2007;Garcia-Ruiz et al, 2011;Verdier and Viollet, 2015). The CMIP5 simulations (Coupled Model Intercomparison Project, Phase 5) expected a mean precipitation decrease of -4%/°C and temperature increase of 20% more than the global average with maximum precipitation reduction reaching -7%/°C in winter in the southern Mediterranean region and -9%/°C in the summer in the Northern region (Lionello & Scarascia, 2018).…”
Section: Introductionmentioning
confidence: 99%